A escrita surda como ela é : estudo da iconicidade em textos de usuários da libras - Cruz, Silvania Dueles da (2017)
The study presents an analysis of the written production of the deaf student user of LIBRAS from the point of view of one of the principles of Functionalism: iconicity. From the manifestations of this principle postulated by North American theorists and the iconic devices mentioned by Taub (2004), the work seeks, insofar as it also presents aspects of the spatial syntax of the Brazilian Sign Language, to identify the sub-functions and iconic motivating devices Of the constructions and syntactic choices that constitute the written production of the deaf user of this modality as L1.The learning of the written mode of the Portuguese language is recognized in this research as a challenge in the classroom and, therefore, the need to understand the motivations of the deaf student in their syntactic constructions in both the signaled and written oral languages. From the analyzes of the records found, the research indicates to proposals and strategies of teaching of the written modality of the Portuguese language that use the iconic relations as a resource that will optimize the learning process.From texts collected in resource rooms, as well as in regular classes of Portuguese Language, shows the most recurrent structures found in said corpus, associating such structures with the iconic devices present in the spatial syntax of LIBRAS, which makes the text of the deaf person Symbolically motivated, characterized by arrangements similar to those of the signaled language.Thus, in addition to promoting a study on the relevance of the iconic subprinciples in the written Portuguese of the deaf student, the work intends to provide a change in the look on their written productions and, through the recognition that the iconic devices present in the LIBRAS are reflected in their Texts, bring those who with such texts have a better understanding of them, that is, to know the Deaf Writing as it is.